Solitary wave solutions of Fitzhugh–Nagumo-type equations with conformable derivatives - Cevikel, Adem C.; Bekir, Ahmet; Abu Arqub, Omar; Abukhaled, Marwan (Frontiers in Physics, 2022)
The Fitzhugh-Nagumo equation is an important nonlinear reaction-di¤usion equation used to model the transmission of nerve impulses. This equation used in biology as population genetics, the Fitzhugh-Nagumo equation is also frequently used in circuit theory. In this study, we given solutions to the fractional Fitzhugh-Nagumo (FN) equation, the fractional Newell-Whitehead-Segel (NWS) equation and the fractional Zeldovich equation. We found the exact solutions of these equations by conformable derivative. With this study, we have obtained new exact solutions within time fractional conformable derivative for these equations.